Accumulation of Heavy Metals (Pb, Cd, V) in Sediment, roots and leaves of Mangrove species in Sirik Creek along the Sea Coasts of Oman, Iran - Musa Keshavarz; Dariush Mohammadikia; Fatemeh Gharibpour; Abdul-Reza Dabbagh (Journal of Applied Sciences and Environmental Management)
Sirik mangrove forests harbour two species, Avicennia marina and Rhizophora macronata living in Azini Creek. Because of a fishing port at Azini Creek, this study was conducted to determine heavy metals concentrations in the Sirik mangrove forests along the Oman Sea coasts. Substantial component analysis of heavy metal concentration in sediments surrounding roots zones of mangrove species showed that Cd and V were negligible, while the Pb concentrations were higher than those found in leaves and roots. Concentrations of Cd and V in the leaves and roots also were negligible.